On the specific status of Hedotettix cristatus Karny, 1915 (Tetrigidae: Tetriginae) - Skejo, Josip; Gupta, Sunil Kumar (Zootaxa, 2015)
Hedotettix cristatus Karny, 1915 is a species described from a single male specimen from Taiwan. Wagan & Kevan in 1992 synonymised the species with Hedotettix punctatus Hancock, 1909. We re-evaluated the specific status of H. cristatus and made a detailed comparison between valuable diagnostic characters. Females of H. cristatus are reported and new localities for the species, found on amateur photos from Taiwan, are presented. H. cristatus stat.rev. is a valid species, endemic to Taiwan, while H. punctatus is a species with a disjunctive distribution, partly in India and partly in China (Hainan, Guangdong, Hubei). The main diagnostic differences between two species are: 1) antennal grooves position: in H. cristatus antennal grooves are situated at the level of the lower margin of the compound eyes or slightly below it, while in H. punctatus, however, antennal grooves are situated slightly above the lower margin of the compound eyes, never at its level or below, 2) scutellum morphology: in H. cristatus, frontal costa bifurcation starts in about upper ¼ of the compound eye height, while in H. punctatus it starts at the level of upper margin of compound eyes or slightly below (with rare exceptions), 3) ratio of femora length/width: H. cristatus is species of robust femora, while H. punctatus has slender femora and 4) prozonal carinae: indistinguishable in H. cristatus, clear and elevated in H. punctatus. H. cristitergus Hancock, 1915 syn.nov. is synonymized with H. punctatus, as already proposed in some old papers.